Effects of Clarias, Soy Protein, Moringa with Vitamin D Biscuit and Anti-TB Drugs on Blood Serum and Biochemical Profile of Tuberculosis-infected Rats - Fariani Syahrul; Annis Catur Adi; Wizara Salisa; Noni Angelina Tazky Aulia; Livia Bellatrix Roberts; Muhammad Atoillah Isfandiari (Universitas Airlangga, 2026)
The surge of tuberculosis (TB) in Indonesia, reaching over 385 cases per 100,000 population in 2024, presents an evident public health challenge. Primary drug-based (OAT/anti-TB drugs) therapy has adverse effects, affecting patient compliance and health outcomes. Nutritional therapy derived from animal-plant protein enriched with vitamin D has been offered as an adjunct therapy. This study investigated the effectiveness of catfish-derived biscuit substitutes, isolated soy protein, and moringa flour enriched with vitamin D in improving physical and immunological outcomes. Using a completely randomized design, the research process encompassed product development and pre-clinical testing in 35 adult white male Rattus norvegicus aged 8 weeks weighing 130-140 grams which were randomly divided into five groups, namely negative control (K0), Mycobacterium tuberculosis (Mtb)-injected (K1), Mtb-injected + OAT (anti-tuberculosis drugs), Mtb-injected + OAT + 1,000 IU vitamin D biscuit (D1), and Mtb-injected + OAT + 2,000 IU vitamin D biscuit (D2), and were observed for a total of 46 days. H37Rv Mycobacterium tuberculosis (Mtb) was injected into as much as 106 colonies/ml of 100 µL. Complete blood count was measured using the HEMAVET method, albumin and total protein were determined using spectrophotometry, and C-reactive protein (CRP) was analyzed using enzyme-linked immunosorbent assay (ELISA). Although product administration did not show a significant impact towards erythrocytes (p>0.05), it was still able to improve BMI within normal limits, increase albumin and total serum protein values, maintain leukocyte, hemoglobin, and hematocrit within standard values, lower CRP levels.